Ceramide in the prostate - Dent, Paul (Landes Bioscience, 2013)
The nomenclature for the serine/threonine protein phosphatases was established by Professor Sir Philip Cohen over 30 years ago.(1) At that time protein phosphatase 1 was known to have two small inhibitory proteins (I-1 and I-2) and be regulated by sub-cellular location whereas no protein inhibitor had yet been discovered for the related multi-subunit phosphatase PP2A. That paradigm subsequently changed, and several PP2A protein inhibitors have been discovered.(2) The protein I2PP2A (SET) is considered to be oncogenic, i.e., PP2A is a tumor suppressor, and is overexpressed in many tumor cell types (ref. 3, and refs. therein). I2PP2A also has other targets besides PP2A, e.g., DNA exonucleases and modification of histone acetylation.(4) PP2A activity is known to be regulated by the bioactive lipid ceramide, and this occurs through both I2PP2A inhibition and PP2A de-repression and through ceramide actions on subunits of the PP2A enzyme complex.(5)(,)(6) In the present manuscript the authors examined the expression of I2PP2A in prostate cancer and prostate epithelial cells. They determined whether ceramide could decrease accumulation of the oncogene c-Myc through inhibition of I2PP2A and activation of PP2A. As I2PP2A is also an inhibitor of histone acetylation they determined whether ceramide could block the epigenetic action of I2PP2A.